Two‐Dimensional Nanostructured Materials for Gas Sensing. (2nd August 2017) - Liu, Xianghong; Ma, Tiantian; Pinna, Nicola; Zhang, Jun
Abstract : Two‐dimensional (2D) nanostructures are highly attractive for fabricating nanodevices due to their high surface‐to‐volume ratio and good compatibility with device design. In recent years 2D nanostructures of various materials including metal oxides, graphene, metal dichalcogenides, phosphorene, BN and MXenes, have demonstrated significant potential for gas sensors. This review aims to provide the most recent advancements in utilization of various 2D nanomaterials for gas sensing. The common methods for the preparation of 2D nanostructures are briefly summarized first. The focus is then placed on the sensing performances provided by devices integrating 2D nanostructures. Strategies for optimizing the sensing features are also discussed. By combining both the experimental results and the theoretical studies available, structure‐properties correlations are discussed. The conclusion gives some perspectives on the open challenges and future prospects for engineering advanced 2D nanostructures for high‐performance gas sensors devices. Abstract : Two‐dimensional (2D) nanostructures are highly attractive for nanodevices due to their high surface‐to‐volume ratio and good compatibility with device design. The most recent advancements in the synthesis, surface engineering, and funcationlization of various 2D nanostructures, including metal oxides, graphene, metal dichalcogenides, phosphorene, BN, and Mxenes for high‐performance gas sensors, are reviewed.